Characterisation and Description of Surface Water Quality in the Threatened Urban Wetlands around the City of Colombo - Hettiarachchi, Missaka; Anurangi, Jayani; de Alwis, Ajith (Journal of Wetlands Ecology, 2011)
Colombo is a city surrounded by a large and interconnected system of natural wetlands. These wetlands which have historically provided a range of water services to the city are now believed to be threatened by degradation due to the recent changes in the urbanization patterns and urban lifestyle in Colombo. This paper presents a study on the current state and recent trends in surface water quality in a selected segment of these wetlands. The study was carried out as a part of a broader multidisciplinary research. The paper consists of a historical analysis of trends in surface water quality parameters and situation analysis of short term spatial and temporal water quality variation in the study area. The research identified that water quality parameters indicating domestic wastewater related pollution showed an increasing trend during the study period. BOD, Phosphates and Fecal Coliform were recorded in levels exceeding the accepted ambient water quality standards. Concentrations of several heavy metals were also above the ambient water quality standards. A distinct difference was observed in water quality between peripheral areas and internal water ways of the wetland. All evidence directs towards severe water quality degradation in the wetland dominated by domestic waste discharges and scattered solid waste dumps. This condition may lead to a nutrient enrichment of the wetland and cause biological and physical responses that may affect adversely on the water services provided. Key words: Water Quality; Urban Wetlands; Wetland Nutrient Enrichment; Water Services; Urban Water Pollution DOI: http://dx.doi.org/10.3126/jowe.v5i0.2831 J Wet Eco 2011 (5): 10-19